Elastic and dimensional properties of newly combined 3D-printed multimaterials fabricated by DLP stereolithography - Kornfellner, Erik; Königshofer, Markus; Unger, Ewald; Moscato, Francesco (Frontiers in Materials, 2023)
In the field of stereolithography 3D printing the portfolio of commercially available photopolymers is growing rapidly. Each material family has its individual properties. However, for some special requirements, there might not be a corresponding product available. This gap that could be closed by combining existing materials. This study aims to predict Young's modulus of specimen manufactured by combining multiple materials using digital light processing (DLP), a subtype of stereolithography. We aim to investigate the effects of the printing process on the geometry and mechanical properties of such 3D printed multimaterials. Using a DLP 3D printer, samples were produced from commercially available pure and mixed materials, and half of the samples underwent post-printing curing. 3-point bending tests were performed to determine the elastic modulus of the samples. The elastic properties have been compared to linear interpolation using the properties of the primary materials. The measurements showed Young's modulus ranging from 1.6 GPa to 2.2 GPa for the post-cured materials, with the mixed materials fitting well with the linear interpolation approach. For 8 out of 9 sample sets, the prediction was within the range of the measurements. In the case of as-printed samples, the elasticity of the primary materials ranged from 0.4 GPa to 0.9 GPa, but all of the mixed materials showed a stiffer behavior than the linear interpolation prediction, up to 57% above the prediction. The dimensions of the printed specimen were measured and groups of different geometrical deviations were identified. These were discussed with regard to the printer system and material mixture. In conclusion, this study shows and discusses the mechanical and dimensional properties of printing results, fabricated with a stereolithographic 3d printer from multiple commercially available primary materials. It shows how to predict the elastic properties of these multimaterials and how to select mixing ratios to achieve specifically desired properties.